Convolution One Dimensional Continuous Function on Fourier Series Expansion - Gunawan, Gani; Respitawulan, Respitawulan; Fikri, Fariz Fahmi (Jurnal Matematika Integratif, 2026)
Convolution is an operation that involves two functions that can be used to transform a continuous input signal at every point in its domain so that a smooth output signal is produced at every point in the domain interval [1],[2]. But what happens when the convolution operation is applied to a function that is expanded through a Fourier series. The series is a series with a basis of differentiable functions, and how to perform convolutions that are expanded through the Fourier series. In this article, we will show a discussion to determine the product of the convolution function on the expansion of the Fourier series and the results obtained. Convolution One Dimensional ContinuousFunction on Fourier Series Expansion